Asset prices, collateral and unconventional monetary policy in a DSGE model - Björn Hilberg; Josef Hollmayr (European Central Bank (ECB), 2011)
In this paper we set up a New-Keynesian model that features an interbank market. The introduction of an interbank market is important to analyze liquidity problems among heterogenous agents within the financial sector. First, because this allows for a situation where increased liquidity supply by the central bank is only partially passed on to the interbank market. Second, this framework allows us to analyze one additional policy measure besides the common interest rate policy undertaken by central banks to alleviate the liquidity shortage on the interbank market. Namely haircuts on eligible assets in repurchase agreements (“Repos”). By varying haircuts applied to securities that serve as collateral in repurchase agreements the stress on the interbank market can be mitigated by bringing down the interest rate charged among banks. Furthermore an exogenous bubble process is modeled which enables us to examine the effects of a deviation of the market price of capital from its fundamental price. This leads to a discussion whether central banks should ”lean against the wind”, i.e. react to deviations of asset prices in the setting of their policy instrument. Finally, this paper tries to shed some light on the “exit strategy” that a central bank should follow after the asset price bubble bursted and the interbank market begins to work properly again.
Keywords: E4; E5; E61; G21; 330; collateral; DSGE; exit strategy; haircuts; monetary policy